Naskah-naskah Moloku Kie Raha: Suatu Tinjauan Umum - Titik Pudjiastuti (Masyarakat Pernaskahan Nusantara, 2016)
Moloku Kie Raha is a term used for referring the four local authorities in Maluku that known as Kolano: Ternate, Tidore, Bacan, dan Jailolo. As a key region in the shipping lanes during the